RUTE PENDISTRIBUSIAN AYAM RAS PEDAGING (BROILER) MENGGUNAKAN METODE FUZZY TOPSIS - Nasution, Nur Sangadah; Sari, Rina Filia (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The broiler farming business in Indonesia continues to grow in order to meet animal protein needs and increase farmers' income. One of the challenges in this negative is determining efficient distribution routes to optimize travel distance and operational costs. Ayam Berkah Sejahtera, a broiler chicken distribution business in North Sumatra, does not yet have optimal routes, so the distribution process is often hampered by travel time and high costs. This research aims to determine the distribution route for broiler chickens using the Fuzzy TOPSIS method. Fuzzy TOPSIS is a multi-criteria decision making method that helps identify the best solution based on the shortest distance from the positive ideal solution and the longest distance from the negative ideal solution. The implementation of this method considers distance, delivery time, vehicle capacity and distribution costs to reach an optimal solution. The analysis results show that Fuzzy TOPSIS has succeeded in increasing the distribution efficiency of Ayam Berkah Sejahtera, speeding up delivery times, and reducing operational costs. This method also provides adjustments in dynamic distribution adjustments, making it suitable for application in multi-criteria distributions. With more optimized distribution routes, companies can achieve better performance and increase customer satisfaction.